ЗНАЧЕННЯ МУТАЦІЇ BRAFV600E ПРИ ІНТРААКСІАЛЬНИХ ПУХЛИНАХ МОЗКУ У ПАЦІЄНТІВ МАЛАЙЗІЇ: СЕРІЯ ВИПАДКІВ І ОГЛЯД ЛІТЕРАТУРИ - Mohamed Yusoff , A.A.; Abd Radzak, S.M.; Mohd Khair, S.Z.N.; Abdullah, J.M. (PH Akademperiodyka, 2023)
Summary. Background: To date, BRAF mutations in brain tumor patients have not been characterized in the Malaysian population. Based on the numerous reported studies, there are main mutations that exist in BRAF gene in various types of cancers. A missense mutation in codon 600 of the BRAF nuclear oncogene (BRAFV600E) is the most prevalent hotspot point mutation that has been identified in multiple human malignancies. Aim: We here aimed to find out the frequency of BRAFV600E mutation in a series of Malaysian patients with brain tumors and if any association exists between BRAFV600E mutation and clinicopathological features of patients. Material and Methods: Fresh frozen tumor tissue samples from 50 Malaysian brain tumor patients were analyzed for BRAFV600E mutational status, and its correlation with clinicopathological features (including age, gender, and tumor localization such as intra-axial: within the brain substance or extra-axial: outside the brain substance) was examined. Results: The overall BRAFV600E mutation frequency was determined to be 22% (in 11 of 50 patients). BRAFV600E was significantly correlated with the tumor location group, which shows BRAFV600E was more frequent in the intra-axial tumor than the extra-axial tumor group. In this study, we also observed that male patients were slightly more susceptible to BRAFV600E mutation, and this mutation was predominant in patients of the age group < 40 years. However, these parameters did not translate to statistical significance. Conclusion: The data demonstrate that BRAFV600E mutation is observed significantly more often in intra-axial brain tumor patients, which can serve as baseline information for further research on genetic alteration that occurs during brain tumor progression in the Malaysian population.